AR‐12 Inhibits Multiple Chaperones Concomitant With Stimulating Autophagosome Formation Collectively Preventing Virus Replication. Issue 10 (6th June 2016) - Booth, Laurence; Roberts, Jane L.; Ecroyd, Heath; Tritsch, Sarah R.; Bavari, Sina; Reid, St. Patrick; Proniuk, Stefan; Zukiwski, Alexander; Jacob, Abraham; Sepúlveda, Claudia S.; Giovannoni, Federico; García, Cybele C.; et al.
Abstract : We have recently demonstrated that AR‐12 (OSU‐03012) reduces the function and ATPase activities of multiple HSP90 and HSP70 family chaperones. Combined knock down of chaperones or AR‐12 treatment acted to reduce the expression of virus receptors and essential glucosidase proteins. Combined knock down of chaperones or AR‐12 treatment inactivated mTOR and elevated ATG13 S318 phosphorylation concomitant with inducing an endoplasmic reticulum stress response that in an eIF2α—dependent fashion increased Beclin1 and LC3 expression and autophagosome formation. Over‐expression of chaperones prevented the reduction in receptor/glucosidase expression, mTOR inactivation, the ER stress response, and autophagosome formation. AR‐12 reduced the reproduction of viruses including Mumps, Influenza, Measles, Junín, Rubella, HIV (wild type and protease resistant), and Ebola, an effect replicated by knock down of multiple chaperone proteins. AR‐12—stimulated the co‐localization of Influenza, EBV and HIV virus proteins with LC3 in autophagosomes and reduced viral protein association with the chaperones HSP90, HSP70, and GRP78. Knock down of Beclin1 suppressed drug‐induced autophagosome formation and reduced the anti‐viral protection afforded by AR‐12. In an animal model of hemorrhagic fever virus, a transient exposure of animals to low doses of AR‐12 doubled animal survival from ∼30% to ∼60% and suppressed liver damage as measured by ATL, GGT and LDH release. Thus through inhibition of chaperone protein functions; reducing the production, stability and processing of viral proteins; and stimulating autophagosome formation/viral protein degradation, AR‐12 acts as a broad‐specificity anti‐viral drug in vitro and in vivo. We argue future patient studies with AR‐12 are warranted. J. Cell. Physiol. 231: 2286–2302, 2016. © 2016 Wiley Periodicals, Inc. Abstract : OSU‐03012 inhibits HSP90 and HSP70 family chaperones which causes enhanced basal levels of endoplasmic reticulum stress and autophagic flux. These biological events collectively result in the destabilization of viral receptors and viral proteins resulting in their degradation. The roles of different chaperones in the replicative potential of viruses as diverse as Measles, HIV, Junin and Ebola has been defined; OSU‐03012 prevents the replication of multiple protease inhibitor resistant strains of HIV. In a rabbit hemorrhagic fever model system, transient exposure to OSU‐03012 reduced animal death and liver damage by over 50%, arguing that the drug has significant anti‐viral activity in vivo.